Development of computational thinking skills through educational robotics - Constantinou, Vaso; Ioannou, Andri (My University, 2018)
Computational thinking (CT) is an important concept in modern education. The scientific community is not only investigating the skills involved in CT but, is also trying to establish how these skills can be developed and through what technological means. Meanwhile, a few studies have investigated the effectiveness of educational robotics (ER) as technological means which can support the development of CT but, issues of measurement of CT (i.e., using validated instruments) seem to hinder the validity of these investigations. In this paper, two quasi-experimental studies were conducted to address students' CT gains linked to their participation in ER activities. The first study was conducted at a primary school in the Eastern Mediterranean; 15 consented students participated in ER activities for five weeks. The second study included 16 students in a secondary school in the same region, who participated in ER activities for three months. Quantitative results, based on a valid measure of CT, showed that the students who participated in the ER interventions demonstrated significant improvement in their CT skills. This study extends the evidence of the potential of using ER to improve students' CT skills in K-12 contexts.
Keywords: Computational thinking; Educational robotics; K-12